Marind Customary Law Practices in Natural Resource Management in Southern Papua - ADV. Neri Aslina (PT. Anagata Sembagi Education, 2025)
This research examines Marind customary law as a normative foundation for sustainable natural resource governance in Southern Papua and evaluates its potential to contribute structurally to Indonesia’s national legal development. Using a normative legal research method, the study analyzes the philosophical, institutional, and jurisdictional principles embedded in Marind eco jurisprudence and assesses their compatibility with statutory environmental law. Results show that Marind norms regulate resource extraction through relational accountability, collective custodianship, and adaptive seasonal management, which have proven effective in biodiversity protection. However, their legal authority remains subordinated to state licensing regimes, resulting in ecological and cultural vulnerability when confronted with external investment interests. The study concludes that integrating Marind jurisprudence through enforceable delegated jurisdiction and the incorporation of customary principles into statutory legislation would strengthen Indonesia’s sustainability law paradigm and advance legal pluralism